Investigating the Impact of Social Media Marketing Efforts on Brand Trus - Kabiri, Morteza; Mohammadi golshad, Leyla; Abbasi, Safora (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The aim of the present study is to investigate the impact of social media marketing efforts on brand trust.Methodology: The research method employed is descriptive and correlational. The statistical population consists of all customers of domestic brand products in Tehran, and due to the large number of individuals, the sample size was estimated at 384 using simple random sampling method and Cochran's formula. The questionnaire was distributed among them. Data collection was done through a questionnaire, the reliability of which was measured and confirmed using Cronbach's alpha reliability and composite reliability methods.Findings: The validity of the tool was examined using construct validity methods (external model), convergent validity (AVE), and discriminant validity. The AVE value for all variables should be greater than 0.5. The research data were analyzed using structural equation modeling method and employing SPSS and AMOS software. The results of the study indicate the confirmation of all hypotheses.Conclusions: The findings suggest that social media marketing efforts, including pattern recognition, consumer panel, and social networks, have a significant impact on brand trust.